Impact evaluation of community based coastal resources management projects in the Philippines. - Pomeroy, R.S., Pollnac, R.B., Predo, C.D., Katon, B.M. (Makati, Philippines ICLARM, 1996)
Fisheries Co-Management Research Project Research Report No.3
Keywords: Coastal resources management; Community